AZ304, a novel dual BRAF inhibitor, exerts anti-tumour effects in colorectal cancer independently of BRAF genetic status. Issue 11 (29th May 2018) - Ma, Rui; Xu, Ling; Qu, Xiujuan; Che, Xiaofang; Zhang, Ye; Fan, Yibo; Li, Ce; Guo, Tianshu; Hou, Kezuo; Hu, Xuejun; Drew, Lisa; Shen, Minhui; et al.
Abstract Background BRAF mutation is associated with poor clinical outcome of patients with malignant tumours, and mediates resistance to chemotherapy and targeted therapy. This study aimed to determine whether V600E mutant and wild type BRAF colorectal cancers exhibit distinct sensitivities to the dual BRAF inhibitor AZ304. Methods Kinase activity was assessed by the AlphaScreen assay. Then, MTT assay, EdU assay, colony-formation assay and Western blot were performed to evaluate the anti-tumour effects of AZ304 in vitro. In vivo efficacy was investigated by xenograft analysis and immunohistochemistry. Results AZ304 exerted potent inhibitory effects on both wild type and V600E mutant forms of the serine/threonine-protein kinase BRAF, with IC50 values of 79 nM and 38 nM, respectively. By suppressing ERK phosphorylation, AZ304 effectively inhibited a panel of human cancer cell lines with different BRAF and RAS genetic statuses. In selected colorectal cancer cell lines, AZ304 significantly inhibited cell growth in vitro and in vivo, regardless of BRAF genetic status. In addition, the EGFR inhibitor Cetuximab enhanced the potency of AZ304 independently of BRAF mutational status. Conclusions The BRAF inhibitor AZ304 has broad spectrum antitumour activity, which is significantly enhanced by combination with Cetuximab in colorectal cancers in vitro and in vivo.